1998
DOI: 10.1046/j.1365-313x.1998.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalisation of the cytoskeleton to plasmodesmata of Chara corallina

Abstract: SummaryThe macromolecular structure of plasmodesmata in the giant celled freshwater alga, Chara corallina, was examined using antibodies against cytoskeletal elements. The large internodal cells of Chara are separated by a nodal complex of smaller cells which are interconnected by plasmodesmata. Putative plasmodesmata-associated proteins can be identified by a comparison of proteins extracted from preparations of clean walls of nodal complexes and those extracted from the external walls of internodal cells whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 43 publications
1
65
0
Order By: Relevance
“…Several other works noted additional internal substructures (Ding et al 1992b, Overall and Blackman 1996. Recently, PD-associated proteins have been identified in charophycean algae and land plants , Blackman and Overall 1998, Gestel et al 2003, Faulkner et al 2005, Sagi et al 2005, Thomas et al 2008, Simpson et al 2009, Faulkner and Maule 2010. These works suggested that there are highly complicated control mechanisms underlying the cell-to-cell molecular traffic via PD.…”
Section: Introductionmentioning
confidence: 98%
“…Several other works noted additional internal substructures (Ding et al 1992b, Overall and Blackman 1996. Recently, PD-associated proteins have been identified in charophycean algae and land plants , Blackman and Overall 1998, Gestel et al 2003, Faulkner et al 2005, Sagi et al 2005, Thomas et al 2008, Simpson et al 2009, Faulkner and Maule 2010. These works suggested that there are highly complicated control mechanisms underlying the cell-to-cell molecular traffic via PD.…”
Section: Introductionmentioning
confidence: 98%
“…Various approaches have been taken to identify such constituents, with limited success (reviewed in Oparka, 2004;Maule, 2008). The proteins identified include cytoskeletal elements (e.g., actin and myosin VIII) (Ding et al, 1996;Blackman and Overall, 1998;Reichelt et al, 1999), proteins associated with the endoplasmic reticulum (e.g., calreticulin) , a protein kinase 1 that phosphorylates Tobacco mosaic virus movement protein (Lee et al, 2005), a 1,3-b-glucanase (Levy et al, 2007b), a class 1 reversibly glycosylated protein (Sagi et al, 2005), and, recently, a receptor-like transmembrane protein located on the plasma membrane in Pds (Thomas et al, 2008). In this article, we report the identification of a family of small glycosylphosphatidylinositol (GPI)-linked proteins that exhibit specific callose binding activity in vitro and that localize to Pds as fluorescent protein fusions.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-to-cell transport occurs through the cytoplasmic space between the plasma membrane and the DT (1,2,4) and also along the ER membrane of the DT (5). Actin and myosin may regulate PD aperture by forming helically arranged particles and spoke-like structures that connect the DT to the plasma membrane (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%